2016
DOI: 10.1051/matecconf/20178702012
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of electrospinning parameter for Poly(L-lactic) acid (PLLA) electrospun nanofiber

Abstract: Abstract. Poly (L-lactic) Acid (PLLA) ia one of the biodegradable polymer that normally used in the biomedical application. In this work it is shown that electrospinning of PLLA electrospun fibre was affected by electrospinning processing parameters such as the solvent systems selection, polymer solution concentration, flow rate and acceleratingvoltage. Optimisation of these parameters is necessary to obtain a beadless and submicron diameter fibre as desired in this research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…1; Table 1). Uniformly produced electrospun nanofibres indicated that electrospinning parameters were optimized accurately [18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…1; Table 1). Uniformly produced electrospun nanofibres indicated that electrospinning parameters were optimized accurately [18][19][20][21] .…”
Section: Resultsmentioning
confidence: 99%
“…Natural fiber is an eco-friendly resource obtained from wood [ 1 ], bamboo [ 2 ], and agricultural waste [ 3 , 4 , 5 , 6 ] such as straw [ 7 ] that comprises cellulose, hemicellulose, lignin and aromatics, waxes and other lipids, ash, and water-soluble compounds [ 8 ]. It is biodegradable, sustainable, economically viable, low density and possesses good specific strengths and moduli [ 9 , 10 , 11 , 12 , 13 , 14 ]. Both the natural filler and polymer matrix used in this study are fully biodegradable at the end of their life cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, acetone as a solvent for PCL was eliminated and polymer concentration was lowered for all materials. Several sources cite this as a method by which fiber diameter can be reduced in electrospun scaffolds 107,126,128,129 . Additionally, the tPU manufacturer recommended polymer solutions between 2 and 7 wt.%.…”
Section: Second Flexible Polymer Trialsmentioning
confidence: 99%